MODEL TGT DENGAN CERDAS CERMAT BERKELOMPOK UNTUK MENINGKATKAN KARAKTER DAN PEMECAHAN PERMASALAHAN MATEMATIKA BANGUN RUANG - Diana Setiani; Yuliana; Nughthoh Arfawi Kurdhi (LPPM Universitas Widya Dharma, 2023)
Learning becomes less interactive when students are learning to build space because they focus more on the teacher's explanations. Students' mathematical character and problem-solving skills cannot be developed by this learning. An alternative for helping pupils improve their mathematical character and problem-solving skills is the TGT learning approach. The two cycles of this classroom action research project are designed to enhance students' mathematical character and problem-solving skills. Group intelligence was used in conjunction with the TGT model at SMP Negeri 4 Klaten class VIII. Students take a pretest to ascertain their starting abilities before class action starts. With only 3% of pupils completing the pretest, the outcomes were still quite poor. Students' ability to solve mathematical problems improved when they took action.Likewise, students' mathematical character has improved, namely in cycle I only 59% of students have mathematical character in the moderate category, while in cycle II as many as 78% of students have mathematical character in the good category.